2019
DOI: 10.3389/fnins.2019.01314
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Spontaneous Neural Activity of the Central Auditory System Changes the Functional Connectivity in the Tinnitus Brain: A Resting-State Functional MRI Study

Abstract: Objective: An abnormal state of the central auditory system (CAS) likely plays a large role in the occurrence of phantom sound of tinnitus. Various tinnitus studies using resting-state functional MRI (RS-fMRI) have reported aberrant spontaneous brain activity in the non-auditory system and altered functional connectivity between the CAS and non-auditory system. This study aimed to investigate abnormal functional connections between the aberrant spontaneous activity in the CAS and the whole brain in tinnitus pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 81 publications
(106 reference statements)
2
12
0
Order By: Relevance
“…In the present study, we found significantly changed (increased or decreased) intranetwork FC within the AUN, aDMN, LFPN, lVN, DAN, and SN in the EG and/or IG compared with the HC group. As an auditory phenomenon, tinnitus has been repeatedly reported to be associated with alterations in the AUN (or auditory regions; Cai, Li, Yang, & Zhang, 2019; Hu et al, 2021; Husain, 2016; Husain et al, 2011; Lan et al, 2021; Schmidt, Akrofi, Carpenter‐Thompson, & Husain, 2013), which indicates the important role of the AUN in tinnitus generation. As the center of the primary auditory cortex, the STG is also considered to be an important multisensory functional brain region that integrates visual, auditory, and language information (Mtui, Gruener, & Dockery, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found significantly changed (increased or decreased) intranetwork FC within the AUN, aDMN, LFPN, lVN, DAN, and SN in the EG and/or IG compared with the HC group. As an auditory phenomenon, tinnitus has been repeatedly reported to be associated with alterations in the AUN (or auditory regions; Cai, Li, Yang, & Zhang, 2019; Hu et al, 2021; Husain, 2016; Husain et al, 2011; Lan et al, 2021; Schmidt, Akrofi, Carpenter‐Thompson, & Husain, 2013), which indicates the important role of the AUN in tinnitus generation. As the center of the primary auditory cortex, the STG is also considered to be an important multisensory functional brain region that integrates visual, auditory, and language information (Mtui, Gruener, & Dockery, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another study proposed that a feedback pathway from the limbic system to the auditory system at the subcortical level may suppress the tinnitus signal (Kraus and Canlon, 2012). A more recent study used functional magnetic resonance imaging (fMRI) to investigate the connection between the auditory network and the limbic system (Cai et al, 2019). Husain et al (2011) suggested a relation between the differential engagement of auditory attention and short-term memory network to the neural bases of chronic tinnitus with hearing loss compared to hearing loss alone.…”
Section: Discussionmentioning
confidence: 99%
“…The tinnitus comorbid with headache may lead to more complex dysfunction in the cortico-limbic network. Moreover, prior fMRI researches have revealed the associations between aberrant neuronal activity and functional connectivity of the STG and tinnitus distress [30][31][32][33][34]. However, Emmert et al found no significant CBF alterations within the auditory cortex in tinnitus patients using ASL [15], partly due to a small sample size (n = 14).…”
Section: Discussionmentioning
confidence: 99%